QTLs associados com emocionalidade em fêmeas pós-parto de camundongos LG/J x SM/J - Monte, Bruno Gabriel Oliveira do (2012)
In mammals, newborns need parental care, mostly maternal care, to succeed in development. Mother emotionality may affect development at initial stages or even emotionality of the offspring in adulthood. In the present study we investigate emotionality, in maternal period, by performing the open field test in mice females from SM/J, LG/J inbred lines and generations F1 and F2 from this intercross. F2 females were also tested in nonmaternal phase. We investigate if F2 females emotionality was associated with variation in weight gain and offspring viability. Finally, we perform QTLs analysis (Quantitative Trait Loci) aiming to study genetic architecture of emotionality at postpartum phase. Ethological analysis indicates that LG/J females seem to have higher level of anxiety when compared to SM/J females. F1 and F2 generations did not show significant differences in most of the phenotypes analyzed. In the contrast between maternal and non-maternal phases of F2 females, it seems females were less anxious in non-maternal phase. In the relationship between anxiety and weight gain among F2 females we observed that several ethological data show significant association with weight gain in some period of life of these females. However, the ethological variations do not seem to interfere in the offspring survival. QTL analysis revealed 11 individual QTLs associated to the phenotypes grooming, immobility, activity at center, and motor activity, that accounts between 5 and 9% of emotionality variation. Beside individual QTLs, we found a total of 88 epistatic QTLs involving the five evaluated phenotypes that together with the individual QTLs explain 24 to 53% of emotionality variation in postpartum females. The present study allowed the identification of putative candidate genes, as well as their relative size effects and patterns of gene action affecting mice emotionality. These results reveal that genetic architecture of emotionality of LG/J x SM/J dams is complex, since indicate the existence of many genes, including the interaction among them in a complex network of epistasis. Besides the genetic basis, is worth noted that environment also have a important impact in emotions through epigenetic mechanisms.